Two new species of Silba (Diptera; Lonchaeidae) from Japan with unusual larval development sites - Macgowan, Iain (Zootaxa, 2020)
Two new species of Silba Macquart, 1851 namely Silba mitsuii sp. nov. and Silba fungicola sp. nov. are described from Japan. The adults of the first species were obtained from larvae found in the flower buds of Camellia japonica L. and of the second from fungal fruiting bodies. This is the first time these types of larval habitat have been recorded for a Silba species.